Microbial Changes Occurring During Oronasal Fistula Wound Healing - Steven L. Goudy; Heath L. Bradley; Camilo Anthony Gacasan; Afra Toma; Keerthi Priya Chinniampalayam Sekar; William M. Wuest; Martin Tomov; Vahid Serpooshan; Ahmet Coskun; Rheinallt M. Jones (Microorganisms)
The oral microbiome is a complex community that matures with dental development and is recognized as a risk factor for systemic disease. Despite the oral cavity having a substantial microbial burden, healing of superficial oral wounds occurs quickly and with little scarring. By contrast, creation of an oro-nasal fistula (ONF), often occurring after surgery to correct a cleft palate, is a significant wound healing challenge. Methods: In this study, we characterized the changes in the oral microbiome of mice following a freshly inflicted wound in the oral palate that results in an open and unhealed ONF. Results: Creation of an ONF in mice significantly lowered oral microbiome alpha diversity, with concurrent blooms of Enterococcus faecalis, Staphylococcus lentus, and Staphylococcus xylosus in the oral cavity. Treatment with oral antibiotics one week before ONF infliction reduced microbiome alpha diversity and prevented E. faecalis, S. lentus, and S. xylosus blooms, but did not impact ONF healing. Conclusions: An ONF in the murine palate leads to a dysbiotic oral microbiome and a bloom of opportunistic pathogens that may prevent ONF healing. Delivery of therapeutics that accelerate ONF healing might restore oral microbiome diversity and inhibit blooms of opportunistic pathogens.